Annealing Effects on Silica Based Optical Waveguides Fabricated by Electron Beam Irradiation - Ary Syahriar (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2014)
Defect in channel waveguide fabricated by e-beam irradiation of PECVD silica-on-silicon films are analyzed by characterizing the propagation constant change due to high temperature annealing. The changes of normalized compaction are also described and the theoretical prediction on the variation of normalized compaction with anneal temperature in isochronal annealing is also provided.